PROVISION OF LEGAL AND REGULATORY PROTECTION IN UKRAINE IN CONDITIONS OF REFORM OF PUBLIC INSTITUTIONS - Сопілко, Ірина Миколаївна; Головня, Ілона Володимирівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2019)
Purpose: in the article authors are exploring modern ways to ensure law and order. Research methods: while writing the article, methods of analysis and synthesis were used. Used comparative method of research. Results: the authors focus on the theoretical approaches to the definition of law and order. The authors agree with the scientists about the need for real compliance with the laws of all strata of society. Discussion: separately, the authors focus on rethinking law and order in Ukraine. The authors believe that in order to overcome legal nihilism in the administrative and law enforcement spheres it is necessary to increase the level of legal awareness of civil servants, which will create conditions for the formation of an appropriate level of legal culture, improvement of legislation, crime prevention, creation of an effective mechanism for protecting the rights of citizens, developing legal reform concepts, affirming the idea respect for the right, ensuring the independence of the state bodies from political decisions. In order to overcome the problems of low efficiency, it is advisable to take measures to eliminate the politicization of the processes of formation and adoption of normative legal acts, continuous monitoring of the current legislation in order to determine the extent and degree of regulatory influence of the relevant legal norm or act in general on social relations, the development and adoption of a lawmaking strategy and its strict observance. The latter must become a deterrent to chaotic, situational rule-making, which ensures the implementation of the principle of legality in the system of public administration [7]. It should also be noted that in order to ensure law and order in the state, first of all, its leaders, lawmakers and all citizens must have a high legal culture and legal consciousness, strictly adhering to the laws, showing an example for imitation, as this guarantees the construction of a strong and organized state.